The Role of Sundanese Ethnic Music in Supporting Creative Economy and Cultural Tourism Development - Ari Maulana Hidayat; Veranus Sidharta (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study examines the role of Sundanese ethnic music as a living cultural heritage that contributes to community well-being, the creative economy, and the development of cultural tourism in Kelapa Nunggal, Bogor, Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, documentation, and NVivo-assisted thematic analysis involving cultural actors at Saung Kalinga. The findings show that Sundanese ethnic music, including Tarawangsa, Karinding, Suling, and gamelan buhun, is not merely perceived as entertainment but as a medium of cultural communication, emotional expression, intergenerational knowledge transmission, and local identity strengthening. Community preferences toward this music are shaped by family memories, childhood experiences, cultural familiarity, social environment, and the calming character of traditional sounds. The study further reveals three interconnected pathways through which ethnic music supports development: an emotional pathway that promotes comfort and stress relief, a cultural pathway that preserves meaning and identity, and a social pathway that encourages participation and collective belonging. These pathways create opportunities for creative performances, cultural products, heritage education, and authentic tourism experiences. The study concludes that Sundanese ethnic music can become a culturally rooted strategy for inclusive and sustainable local development in contemporary rural communities.